2015
DOI: 10.1159/000441349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FGFR Signaling on Cell Proliferation and Differentiation of Apert Dental Cells

Abstract: The Apert syndrome is a rare congenital disorder most often arising from S252W or P253R mutations in fibroblast growth factor receptor (FGFR2). Numerous studies have focused on the regulatory role of Apert FGFR2 signaling in bone formation, whereas its functional role in tooth development is largely unknown. To investigate the role of FGFR signaling in cell proliferation and odontogenic differentiation of human dental cells in vitro, we isolated dental pulp and enamel organ epithelia (EOE) tissues from an Aper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Interestingly, FGFR‐related signaling pathways are also believed to play essential roles in tooth development . It is not surprising therefore to find dental abnormalities associated with this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, FGFR‐related signaling pathways are also believed to play essential roles in tooth development . It is not surprising therefore to find dental abnormalities associated with this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…FGFR1 is known as a major factor affecting cell proliferation and differentiation. 34 Thus, the enhanced FGFR1 expression in the presence of RG-I could contribute to greater bone regeneration following the P. gingivalis infection. The present study also demonstrated the ability of RG-Is, particularly PA, to suppress the MMP2 expression in the presence of P. gingivalis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical investigation has demonstrated the important role of the FGF/FGFR signaling in the promotion of bone regeneration. FGFR1 is known as a major factor affecting cell proliferation and differentiation . Thus, the enhanced FGFR1 expression in the presence of RG‐I could contribute to greater bone regeneration following the P. gingivalis infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been mentioned that the probability of a second child being affected is 1%, and that a person with AS has a 50% risk of having a child with the syndrome ( 8 ). The FGFR are a family of mitogenic signaling molecules that play an important role on the control of cell proliferation and survival ( 1 ); thus, in AS, fibroblasts are not able to produce the essential fibrous material in several craniofacial tissues, including bone sutures and cartilage, and during tooth formation and regeneration ( 4 , 18 , 20 - 22 ); thus, the mutated FGFR2 gene may influence the dental abnormalities observed in AS ( 21 ).…”
Section: Introductionmentioning
confidence: 99%